L’irrationalité dans la prise de décision individuelle: deuxième partie - Fournier, Geneviève; Bujold, Charles (Canadian Journal of Counselling and Psychotherapy, 2012)
In this article, the authors bring out some irrational aspects of individualdecision-making and some irrational factors that might influence the individualduring this process. New theoretical perspectives are then proposed, and somepractical and research implications are suggested.